(Dielectrical Properties of Agricultural Produce and Factors which Affect the Non-Destructive Analysis Method) - Sudibyo, Agus (Balai Besar Industri Agro, 1994)
Destructive analysis mathod had been developed in order to reduce the amount of samples used and to increase the efficiency.Several material properties of agricultural produce are known to have relations with their dielectrical properties.These relationship have been studied and in intruments for the purpose of analysis have been developed.The dielectrical properties of agricultural produce are affected by several factors such as frequency,temperature,density,and their composition.